The French compassionate programme of elexacaftor/tezacaftor/ivacaftor in people with cystic fibrosis with advanced lung disease and no F508del CFTR variant - Burgel, Pierre-Régis; Sermet-Gaudelus, Isabelle; Durieu, Isabelle; Kanaan, Reem; Macey, Julie; Grenet, Dominique; Porzio, Michele; Coolen-Allou, Nathalie; Chiron, Raphael; Marguet, Christophe; Douvry, Benoit; Dufeu, Nadine; et al. (The European respiratory journal, 2023)
The European Medicines Agency has approved the cystic fibrosis transmembrane conductance regulator (CFTR) modulator combination elexacaftor/tezacaftor/ivacaftor (ETI) for people with cystic fibrosis (CF) carrying at least one F508del variant. The United States Food and Drug Administration (FDA) also approved ETI for people with CF carrying one of 177 rare variants. An observational study was conducted to evaluate the effectiveness of ETI in people with CF with advanced lung disease who were not eligible for ETI in Europe. All patients with no F508del variant and advanced lung disease (defined as having a percent predicted forced expiratory volume (ppFEV ) <40% and/or being under evaluation for lung transplantation) and enrolled in the French compassionate programme initiated ETI at recommended doses. Effectiveness was evaluated by a centralised adjudication committee at 4-6 weeks in terms of clinical manifestations, sweat chloride concentration and ppFEV . Among the first 84 people with CF included in the programme, ETI was effective in 45 (54%), and 39 (46%) were considered to be nonresponders. Among the responders, 22 (49%) out of 45 carried a variant that is not currently approved by the FDA for ETI eligibility. Important clinical benefits, including suspending the indication for lung transplantation, a significant decrease in sweat chloride concentration by a median (interquartile range (IQR)) -30 (-14--43) mmol·L (n=42; p<0.0001) and an improvement in ppFEV by +10.0 (6.0-20.5) percentage points (n=44; p<0.0001), were observed in those for whom treatment was effective. Clinical benefits were observed in a large subset of people with CF with advanced lung disease and variants not currently approved for ETI.